Characterisation and beneficiation of Indian coking coal washery fines. (2015) - Jena, M.S.; Priyadarsini, A.; Dash, P.; Mohanty, J.K.
Demand of coking coal is very high in Indian steel sector. But unfortunately, the reserve is meagre. Hence, beneficiation of coking coal fines is most essential. The present study reports the beneficiation of fines generated at a coking coal washery in Eastern India. The fines contain 32.8% ash, 17.9% volatile matter and 49.6% fixed carbon. Characterisation study reveals that quartz is the major gangue mineral followed by illite and hematite. ΣREE content of the sample is around 200 ppm. By conventional cell flotation, it is possible to get a clean coal with 14.0% ash with 71.6% yield and 89.5% combustible recovery. Further, the ash is reduced to 12.5% at 72.4% yield by column flotation. The tailing containing more REE and radioactive elements may be considered as an alternative REE source. Release analysis was carried out to evaluate the performance of cell and column flotation. [Received: April 4, 2014; Accepted: November 7, 2014]